Dampak Kebijakan Bea Masuk Tindakan Pengamanan terhadap Proteksi dan Daya Saing Produk Baja Lapis Aluminium Seng - Syariful Anam; Akhmad Solikin (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2020)
Safeguard measures is a trade remedies policies regulated by World Trade Organization (WTO) to recover loss (injury) suffered by domestic industries as a result of liberalization in international trade, as an instrument to protect and increase competitiveness of domestic industries which are still at infant industry stage. In Indonssia, the steel industry sector is designated as a national priority so that its growth must be maintained. Meanwhile, the import surge phenomenon of flat-rolled products from iron or non-alloy steel has threatened the existence of domestic steel industries which produce similar commodities. The Indonesian government responded by setting the Safeguard Measures policy, with the hope that the industry would make structural adjustments during the imposition period so that its competitiveness could be increased. This study uses monthly import data from January 2012 to December 2018 to determine whether the Safeguard Measures has been effective as a protection instrument. To measure competitiveness, Revealed Comparative Advantage (RCA) method and Trade Specialization Index (TSI) were used. The results of this study show that the policy reduced the import of the same and similar steel products which meant it is effective as an instrument of protection. In addition, there has been an increase in competitiveness even though Indonesia is still a net importer.